Conquering the Stormy Seas of Pandemic: Appropriateness and Effectiveness of a Quasi-Military Institution's Covid-19 Response - Victoria Paraggua; Froilan Mobo; Ronalyn Acuavera; Leah Villavicencio; Sheena Lee Atejera; Geraldine Pasa (Philippine Association of Institutions for Research, Inc., 2021)
The global health crisis brought about by the COVID-19 has disrupted and negatively affected even the education sector. Strict measures and plans to curb the spread of the virus were implemented nationwide, but a sudden surge of COVID-19 positive cases at the Philippine Merchant Marine Academy was experienced. Thus, this research generally aimed to discover how PMMA responded to the surge in terms of effectivity and appropriateness. This quantitative-descriptive research used a bilingual researcher-made survey questionnaire. Through the descriptive analysis of the data gathered, the study found out that the measures implemented (e.g., adequate meals for the stay-in respondents, consultation with relevant personnel, ensuring strict compliance with health and safety protocols.) were generally highly appropriate and highly effective. Even so, some practices must be corrected to ensure the safety of cadets and employees, including strict implementation/compliance to health and safety protocols, guidelines on quarantine facilities, and allowing COVID-19 negative students to stay inside the Academy. Given these, to ensure resiliency to future and similar circumstances, it is recommended that cadets who were sent outside for important reasons must be quarantined, a permanent emergency management team be created, a work from the home scheme will be implemented, and vaccination of all employees and cadets will be worked on.